Functional Constipation and Constipation-Predominant Irritable Bowel Syndrome in the General Population: Data from the GECCO Study. (31st December 2015) - Enck, Paul; Leinert, Johannes; Smid, Menno; Köhler, Thorsten; Schwille-Kiuntke, Juliane
Abstract : Background . The prevalence of constipation in the (German) population has been shown to be 14.9% in a telephone survey, but more detailed data are required to characterize the sociographics and clinical characteristics of persons with different types of functional constipation, either constipation-predominant irritable bowel syndrome (IBS-C) or functional constipation with or without meeting Rome criteria. Methods . Of 2239 constipated individuals identified during the telephone interview, 1037 (46.3%) were willing to provide a postal address for a questionnaire, of which 589 (56.8%) returned the questionnaire, inquiring about sociographic data, clinical symptoms, and health care behavior related to constipation, as well as health-related quality-of-life (SF12). Subgroups of functionally constipated individuals were compared. Results . More than 50% of the respondents reported a somatic comorbid condition and/or regular medication intake that may contribute to constipation. We split the remaining individuals (N = 214 ) into three groups, matching Rome-criteria for IBS (IBS-C, n = 64 ) and for functional constipation (FC-R, n = 36 ) and FC not matching Rome criteria (n = 114 ). Nearly all sociographic and clinical characteristics were equal among them, and all individuals with constipation had similar and lowered QOL on the SF-12 physical health domain, but in IBS-C the scores were also significantly lower in comparison to FC-R and FC, in both the physical health and the mental health domain. Conclusion . Only a fraction of individuals with chronic constipation match Rome criteria for IBS-C or FC, but subgroups do not differ with respect to most other measures except quality-of-life profiles.